Aesthetic Function of the Attributes "Aḥad" and "Ṣamad" in the Quran: A Structuralist and Statistical Stylistic Analysis - Ahmad Arefi; Habibollah Yazdani (قرآن فرهنگ و تمدن)
In the Quran, the attributes "Aḥad" and "Ṣamad" are endowed with a distinct aesthetic structure, which reflects their significance within the frameworks of substitution and combination. These attributes underscore the absolute oneness and self-sufficiency of Allah, while simultaneously highlighting the dependence of all creation on Him. This study employs a descriptive-analytical methodology, incorporating structuralism and statistical stylistics, with a focus on Saussurean theory, to explore the aesthetic implications of the attributes "Aḥad" and "Ṣamad" in the Quran. The attribute "Aḥad" appears 73 times in the Quran, but is used solely once as an attribute of Allah in the first verse of Surah Al-Ikhlas, where it is presented in a nominal, affirmative sentence structure. Here, it functions rhetorically to emphasize Allah's uniqueness, remaining ineffable and distinct from all other entities. In contrast, "Ṣamad" is used only once in the Quran, in the second verse of Surah Al-Ikhlas. This term is also employed as an attribute of Allah, placed within a nominal, affirmative sentence structure, accompanied by the definite article and the restrictive particle, thereby asserting the existence of a singular, eternal, and self-sufficient being—Allah. The representation of these concepts, derived from the attributes "Aḥad" and "Ṣamad," is examined through the lens of structuralism, focusing on the axes of substitution and combination as outlined by Saussure. The interplay of these attributes, particularly in their collocation with the terms "He" and "Allah," and the repetition of "Allah," serves to reinforce their interdependence, highlighting the mutual validation of these attributes in affirming Allah's oneness through His self-sufficiency. Furthermore, the attribute "Ṣamad" not only asserts Allah's perpetual self-sufficiency but also strengthens the notion of His eternal oneness.